Electric vehicle battery systems - Dhameja, Sandeep (Boston : Newnes, 2001)
Electric Vehicle Battery Systems provides operational theory and design guidance for engineers and technicians working to design and develop efficient electric vehicle (EV) power sources. As Zero Emission Vehicles become a requirement in more areas of the world, the technology required to design and maintain their complex battery systems is needed not only by the vehicle designers, but by those who will provide recharging and maintenance services, as well as utility infrastructure providers. Includes fuel cell and hybrid vehicle applications. Written with cost and efficiency foremost in mind, Electric Vehicle Battery Systems offers essential details on failure mode analysis of VRLA, NiMH battery systems, the fast-charging of electric vehicle battery systems based on Pb-acid, NiMH, Li-ion technologies, and much more. Key coverage includes issues that can affect electric vehicle performance, such as total battery capacity, battery charging and discharging, and battery temperature constraints. The author also explores electric vehicle performance, battery testing (15 core performance tests provided), lithium-ion batteries, fuel cells and hybrid vehicles. In order to make a practical electric vehicle, a thorough understanding of the operation of a set of batteries in a pack is necessary. Expertly written and researched, Electric Vehicle Battery Systems will prove invaluable to automotive engineers, electronics and integrated circuit design engineers, and anyone whose interests involve electric vehicles and battery systems. * Addresses cost and efficiency as key elements in the design process * Provides comprehensive coverage of the theory, operation, and configuration of complex battery systems, including Pb-acid, NiMH, and Li-ion technologies * Provides comprehensive coverage of the theory, operation, and configuration of complex battery systems, including Pb-acid, NiMH, and Li-ion technologies.
Machine generated contents note: ACKNOWLEDGMENTS ix -- 1: ELECTRIC VEHICLE BATTERIES -- Electric Vehicle Operation -- Battery Basics -- Introduction to Electric Vehicle Batteries -- Fuel Cell Technology -- Choice of a Battery Type for Electric Vehicles -- 2: ELECTRIC VEHICLE BATTERY EFFICIENCY -- Effects of VRLA Battery Formation on Electric Vehicle Performance -- Regenerative Braking -- Electric Vehicle Body and Frame -- Fluids, Lubricants, and Coolants -- Effects of Current Density on Battery Formation -- Effects of Excessive Heat on Battery Cycle Life -- Battery Storage -- The Lithium-ion Battery -- Traction Battery Pack Design -- 3: ELECTRIC VEHICLE BATTERY CAPACITY -- Battery Capacity -- The Temperature Dependence of Battery Capacity -- State of Charge of a VRLA Battery -- Capacity Discharge Testing of VRLA Batteries -- Battery Capacity Recovery -- Definition of NiMH Battery Capacity -- Li-ion Battery Capacity -- Battery Capacity Tests -- Energy Balances for the Electric Vehicle -- 4: ELECTRIC VEHICLE BATTERY CHARGING -- Charging a Single VRLA Battery -- Charge Completion of a Single VRLA Battery -- Temperature Compensation During Battery Charging -- Charging NiMH Batteries -- Rate of Charge Effect on Charge Acceptance Efficiency of Traction -- Battery Packs -- Environmental Influences on Charging -- Charging Methods for NiMH Batteries -- Charging Technology -- Battery Pack Corrective Actions -- 5: ELECTRIC VEHICLE BATTERY FAST CHARGING -- The Fast Charging Process -- Fast Charging Strategies -- The Fast Charger Configuration -- Using Equalizing/Leveling Chargers -- Inductive Charging-Making Recharging Easier -- Range Testing of Electric Vehicles Using Fast Charging -- Electric Vehicle Speedometer Calibration -- 6: ELECTRIC VEHICLE BATTERY DISCHARGING -- Definition of VRLA Battery Capacity -- Definition of NiMH Battery Capacity -- Discharge Capacity Behavior -- Discharge Characteristics of Li-ion Battery -- Discharge of an Electric Vehicle Battery Pack -- Cold-Weather Impact on Electric Vehicle Battery Discharge -- 7: ELECTRIC VEHICLE BATTERY PERFORMANCE -- The Battery Performance Management System -- BPMS Thermal Management System -- The BPMS Charging Control -- High-Voltage Cabling and Disconnects -- Safety in Battery Design -- Battery Pack Safety-Electrolyte Spillage and Electric Shock -- Charging Technology -- Electrical Insulation Breakdown Detection -- Electrical Vehicle Component Tests -- Building Standards -- Ventilation -- 8: TESTING AND COMPUTER-BASED -- MODELING OF ELECTRIC VEHICLE BATTERIES -- Testing Electric Vehicle Batteries -- Accelerated Reliability Testing of Electric Vehicles -- Battery Cycle Life versus Peak Power and Rest Period -- Safety Requirements for Electric Vehicle Batteries --APPENDIX A: FUEL CELL PROCESSING -- TECHNOLOGY FOR TRANSPORTATION -- APPLICATIONS: STATUS AND PROSPECTS -- APPENDIX B: VEHICLE BATTERY CHARGING -- CHECKLIST/LOG -- APPENDIX C: DAY 1/2/3 RANGE AND CHARGE TEST LOG -- APPENDIX D: SPEEDOMETER CALIBRATION -- TEST DATA LOG -- APPENDIX E: ELECTRIC VEHICLE PERFORMANCE TEST -- SUMMARY -- BIBLIOGRAPHY.
Includes bibliographical references (p. 215-219) and index.
Keywords: Electric automobiles -- Batteries; Electric vehicles -- Power supply; Electronic books